Demystifying the Self: Metaphors of Sin and Self-Sacrifice in Miura Ayako’s Early Novels - Ryota Sakurai (Japanese Language and Literature)
This essay examines an alternative to dominant postwar notions of subjectivity in the Japanese cultural sphere through an analysis of Miura Ayako’s mid-1960s novels: Hyōten (Freezing Point, 1964), Hitsujigaoka (Hill of Sheep, 1965), and Shiokari tōge (Shiokari Pass, 1966). It argues that Miura’s depictions of sin and self-sacrifice serve as metaphors that critique prevailing ideas of subjectivity. Her doubly minoritized position as a female writer and a Christian significantly shapes this counternarrative while simultaneously complicating its construction and expression. Drawing on Iida Yūko’s conception of ōtōsei (responsiveness) and hidokusei (being read), the essay examines the discursive stakes of Miura’s fiction. Her work debunks the myth of self-contained individuals and presents the self neither as an idealized autonomous agent nor as doomed to a precarious existence, but as relational, inherently engaged in efforts toward reconciliation with others. This counter-vision unfolds in her novels through metaphors of sin and self-sacrifice, framed within the popular domestic novel form of the 1960s.